2005
DOI: 10.1186/1743-422x-2-32
|View full text |Cite
|
Sign up to set email alerts
|

Eco-epidemiological analysis of dengue infection during an outbreak of dengue fever, India

Abstract: Background: This study was designed to find out a relationship of dengue infection with climatic factors such as rainfall, temperature and relative humidity during the dengue fever epidemic in the year 2003. Blood samples were collected from 1550 patients experiencing a febrile illness clinically consistent with dengue infection. Serological confirmation of Dengue Infection was done using Dengue Duo IgM and IgG Rapid Strip test (Pan Bio, Australia), which detected dengue-specific antibodies. Monthly data of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
2
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(41 citation statements)
references
References 10 publications
4
32
2
3
Order By: Relevance
“…It has risen to epidemic proportions and is endemic to many areas, both urban and rural. In our study highest prevalence was seen in the age groups between 11-50 years and with male preponderance which is seen in other studies also (Gupta et al, 2006;Chakravarti et al, 2005;Sarkar et al, 2012). The sensitivity of the rapid ICT tests for NS1 Ag& IgM in our study was more than 90%, and specificity more than 98% when compared to ELISA.…”
Section: Resultssupporting
confidence: 70%
“…It has risen to epidemic proportions and is endemic to many areas, both urban and rural. In our study highest prevalence was seen in the age groups between 11-50 years and with male preponderance which is seen in other studies also (Gupta et al, 2006;Chakravarti et al, 2005;Sarkar et al, 2012). The sensitivity of the rapid ICT tests for NS1 Ag& IgM in our study was more than 90%, and specificity more than 98% when compared to ELISA.…”
Section: Resultssupporting
confidence: 70%
“…In this study age wise distribution showed the involvement of all age groups with significant number in adults of 21-30 years in comparison to children and people above 50 years of age. Other countries of south Asia also showed similar findings of infection in same age group 21-30 years (Chakravarti & Kumaria, 2005). Age group 21-30 years was also seen prominent in some previous studies in India.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, the daily minimum temperature and an increase in the rainfall from the previous month were associated with increase in the larval abundance [20]. Thus there is a collective contribution of temperature and humidity on dengue outbreaks triggered by the feeding activity, survival and development of vectors [21]. …”
Section: Introductionmentioning
confidence: 99%